Vitamin C inhibit upregulation of plasma and joint interleukin-1β level in cold stress-exposed adjuvant arthritis - Fitri Handajani; Sulistiana Prabowo (Biomedical Engineering, 2016)
Objective:  We aimed to investigate whether cold stress increased plasma and joint IL-1β and whether vitamin C quenched ROS and reduced increased IL-1β. Secondly whether there is any correlation between plasma and joint IL-1βlevel.Material and methods:  Male adjuvant arthritic rats (age=10-12 weeks; n=8/group) were exposed to cold stress (5oC for 15 minutes/day for 7 days) with/without vitamin C (50 mg/day orally) and then kept for 14 days. The control group did not receive either cold exposure or vitamin C. Plasma IL-1βlevel was measured using indirect ELISA and joint IL-1β was measured using imunohistochemistry before treatment, day 0, 7, 14 after treatment.Result:  Cold stress significantly increased plasma IL-1β level directly after cold stress (p=0.025), 14 days after cold stress (p=0.002). Cold stress significantly increased percentage area positive of joint IL-1β day 7 (p=0.001), day 14 (p=0.001). Compared to controls vitamin C significantly reduced plasma and joint IL-1β directly after cold stress, day 7, 14 after cold stress (p< 0.05). No significant correlation between plasma and joint IL-1β in all groups (p>0.05).Conclusion:  Cold stress increased plasma and joint IL-1β and vitamin C reduced increased IL-1β  possibly by reducing ROS production and NF-kB activation.